Health Risk Assessment of Polycyclic Aromatic Hydrocarbons in Surface Soils at North Baiji City, Iraq. - F. Abed, Mahmood; M. Ali, Sawsan; S. Altawash, Balsam (Iraqi Journal of Science, 2023)
Four major factories (Petroleum Refineries Company, Detergents Plant, Thermal Power Plant, and Gaseous Power Plant) are located to the north of Baiji City. They release pollutants in form of gases, liquids and solids; they find their way to the surrounding environment. To assess the environmental pollution of the area, 18 samples of surface soil distributed around the industrial establishments were collected and analyzed to determine the concentration of polycyclic aromatic hydrocarbons (PAH) components which are often targets in the environmental checking. Identification and quantification of the 16 PAHs components was accomplished using High Performance Liquid Chromatography (HPLC) had a model Shimadzu LC-10 AVP. The total concentrations of 16 PAHs were ranged from (94.9) to (416.3) μg/kg with an average value of (217.5) μg/kg. The most abundant PAHs was Fluorene followed by Acenaphthylene, Naphthalene, Chrysene, Phenanthrene, Benzo(b)fluora-nthene, Fluoranthene, Benzo(a)anthracene, Benzo(a)pyrene, Benzo(g,h,i)perylene, Dibenzo(a,h)anthracene, Indeno(1,2,3-cd) pyrene, Pyrene, Acenaphthene, Anthracene, and Benzo(k)fluoranthene.Seven possible carcinogenic PAHs (Σ7c-PAHs) accounted 38.9 % to the total PAHs. The petroleum combustion and biomass combustion were the main sources of PAHs in the surface soil. The mean values of cancer risk levels for children via ingestion, dermal contact, and inhalation were (6.02*10-7), (7.51*10-7) and (5.91*10-12) respectively, suggesting no potential health hazards, while these for adults were (1.78*10-6), (3.16*10-6) and (1.40*10-10) respectively, implying potential health risks via ingestion and dermal contact, but not via inhalation exposure. The total value of ILCRing+drm+inh for children and adults via three exposure pathways were (2.43*10-5) and (8.90*10-5) respectively, indicating potential health risks.